'There's an App for That!' Writing Technology Reviews for Academic Journals. (April 2022) - Kohnke, Lucas; Moorhouse, Benjamin Luke
Technology reviews are becoming an increasingly common genre within English language teaching and learning journals. This is due to the proliferation of technologies and their affordance in language learning. Although journals provide editorial guidelines for how to write technology reviews, they can be quite general. This short article offers some practical considerations and ideas, and includes published technology review as an example in the online appendix, showing the rhetorical moves for writing technology reviews in the field of English language teaching and learning.